2020
DOI: 10.22435/hsr.v23i1.2594
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Mempengaruhi Kejadian Tuberkulosis pada Umur 15 Tahun ke Atas di Indonesia

Abstract: Today, Pulmonary Tuberculosis still remains a notable health concern in Indonesia. Pulmonary Tuberculosis (called TB) is a disease of ancientness who determined by numerous factors. These factors are relating to host, including age, sex, race, socioeconomic, lifestyle, marital status, work, heredity, nutrition and immunity. This study aimed to fi nd out on infl uence factors pulmonary tuberculosis occurrence of 15 years old or above in Indonesia, according to the Tuberculosis Prevalence Survey Data Year 2013-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
23

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 3 publications
1
9
0
23
Order By: Relevance
“…However, the analysis results showed that the age group>55 years had a 1.15 times more risk of contracting TB than those aged 19-54 years. This is almost the same as previous studies, where the age group> 55 years has 1.7 times more risk of suffering from TB than those aged 15-34 years (Pangaribuan et al, 2020) The results of this study showed that the number of men who had been diagnosed with TB by a doctor in one year was more (58%) and had a 2.4 times risk of contracting TB than women.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…However, the analysis results showed that the age group>55 years had a 1.15 times more risk of contracting TB than those aged 19-54 years. This is almost the same as previous studies, where the age group> 55 years has 1.7 times more risk of suffering from TB than those aged 15-34 years (Pangaribuan et al, 2020) The results of this study showed that the number of men who had been diagnosed with TB by a doctor in one year was more (58%) and had a 2.4 times risk of contracting TB than women.…”
Section: Resultssupporting
confidence: 90%
“…Another study showed that nutritional status is one of the factors associated with tuberculosis at ≥15 years of age in Indonesia. (Rukmini & Chatarina, 2011) (Pangaribuan et al, 2020) Likewise, in Rahmi's research, 63% of TB sufferers have an underweight nutritional status. (Surakhmi Oktavia, Rini, n.d.) The Kannan study showed that 90.54% of 74 TB patients were underweight.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Karakteristik manusia bisa berupa faktor genetik, umur, jenis kelamin, pekerjaan, kebiasaan dan status sosial ekonomi [20]. Hasil penelitian dari pangaribuan, L [40] menyatakan bahwa Kejadian TB pada partisipan yang berumur 15 tahun ke atas dipengaruhi beberapa faktor seperti: faktor umur, jenis kelamin, daerah tempat tinggal, pendidikan, dan kawasan. Selain itu juga dipengaruhi faktor lain, seperti: apakah pernah tinggal dengan penderita TB, pernah didiagnosisis TB paru oleh tenaga kesehatan, pernah didiagnosis DM oleh dokter, dan merokok.…”
Section: Pendahuluanunclassified